Preliminary investigation of sleep-related driving fatigue experiment in Indonesia - Sanjaya, Kadek Heri; Kusuma Sya'Bana, Yukhi Mustaqim; Hutchinson, Shaun; Diels, Cyriel (Journal of Mechatronics, Electrical Power and Vehicular Technology, 2018)
Sleep-related driving fatigue has been recognised as one main cause of traffic accidents. In Indonesia, experiment-based driving fatigue study is still very limited, therefore it is necessary to develop laboratory-based experiment procedure for sleep-related fatigue study. In this preliminary study, we performed a literature review to find references for the procedure and three pilot experiments to test the instruments and procedure to be used in measuring driving fatigue. Three subjects participated, both from experienced and inexperienced drivers. Our pilot experiments were performed on a driving simulator using OpenDS software with brake and lane change test reaction time measurement. We measured sleepiness by using Karolinska Sleepiness Scale (KSS) Questionnaire. The conditions of the experiment were based on illumination intensity as well as pre- and post-lunch session. We found that lane change reaction time is more potential than brake reaction time to measure driving performance as shown by the more fluctuating data. Post-lunch seems to induce drowsiness greater than illumination intensity. KSS questionnaire seems non-linear with driving performance data. We need to test further these speculations in the future studies involving a sufficient number of subjects. We also need to compare the effect of circadian rhythm and sleep deprivation on driving fatigue. The use of eye closure and physiological measurement in further study will enable us to measure driving fatigue more objectively. Considering the limitations, more preliminary experiments are required to be performed before conducting the main experiment of driving fatigue.